Simulação numérica da formação de produtos da combustão utilizando óleo diesel misturado com biocombustível - Aquino Júnior, Airton Patricio de (2019)
Environmental monitoring organizations now set strict criteria for combating atmospheric pollution, which must be met by consumers of fossil fuels. These criteria aim to minimize the action of products from the burning of fuels to nature. The present work aims to present a computational tool capable of estimating the concentrations of the gases produced during the combustion of diesel fuel mixtures with biofuel. For this, the coupling of a two-zone thermodynamic model proposed by HEIDER (1996) to the onedimensional, quasi-static thermodynamic simulation model proposed by CLUME (2018) is used, and to determine product concentrations, the methodologies of equilibrium and chemical kinetics. Finally, in order to calibrate the model developed with experimental data, the Leverberg-Marquardt optimization method was used to determine the adjustment coefficients. The final difference between experimental and corrected values was minimized under the conditions of 1500 and 2000 rpm for all fuel biofuel contents, validating the model under these conditions for CO2 and NOx gases. With respect to CO, the proposed coefficients of adjustment need to be improved.